Green Economy Improves SME Performance Through Green Organizational Citizenship Behavior - Asmar; Fajriani Azis; Rudi Salam; Hillman Wirawan; Aris Baharuddin (Jurnal Manajemen, 2026)
This study examines how a green-economy orientation enhances sustainable business performance through the mediating role of Green Organizational Citizenship Behavior (GOCB) among employees of Indonesian SMEs. As SMEs face rising expectations to embed environmental sustainability in daily operations, identifying behavioral mechanisms that translate green initiatives into performance gains is essential. Integrating the Resource-Based View and Dynamic Capabilities with Social Exchange Theory, the study explains how green-economy practices can strengthen employees’ voluntary pro-environmental behaviors, thereby improving business outcomes. Using a quantitative design, data were collected from 220 SMEs in South Sulawesi and analyzed with Structural Equation Modeling (SmartPLS 4). The findings show that green-economy orientation positively affects GOCB, and GOCB significantly mediates the relationship between green-economy practices and sustainable business performance. These results underscore employees’ discretionary green actions as a key lever for managers and policymakers seeking sustainability-driven competitiveness.